About the company for you and educate the living together run colleges in Bogotá - Alexander Orobio Montaño (Corporación Universitaria Minuto de Dios, 2014)
This document discusses the determinants of a deteriorating co-existence and life among different schools in Bogotá. To this effect, the document considers the transformation of the State through political and economic reforms that Colombia as well as Latin America, adopted in the nineties in preparation for the big global economic reform known as globalization. Similarly, the discussion focuses on educational reforms and the new conception of education that emerge from the constitution of 1991 in Colombia and its potential impact on school interaction from the perspective of educational institutions survey in Bogotá on school life and the circumstances that affect it as addressed by the National Department of Statistics "DANE" in agreement with the Secretariat of the State Education.